Analysis of Sustainable Awareness of Junior High School Students on Biotechnology Material - Nengsih Kumala Sari; Leny Heliawati; Bibin Rubini (Yayasan Keluarga Guru Mandiri, 2024)
SDGs are a UN program that covers many important world issues, including education. Integrating science learning with Education for Sustainable Development (ESD) aims to increase students' understanding of (SDGs) and foster sustainability awareness so that they can be implemented in life. The purpose of this study was to collect preliminary information about the profile of sustainability awareness on SDG 6 and SDG 12 of junior high school students in grade IX related to Biotechnology material. This research used a descriptive qualitative method; the sample consisted of 71 students who were given a closed questionnaire of 20 statements. The sustainability awareness profile studied consists of three categories: behavioral and attitudinal awareness, emotional awareness, and sustainability practice awareness. The results showed that students have a level of sustainability awareness of SDGs with an average score of 2.9 out of 4, so it is included in the high criteria. Other results show that students' sustainability awareness of SDG 6 is higher than SDG 12, with an average ratio of 3.1 and 2.9. Meanwhile, sustainability awareness of the SDGs for female students is relatively higher than for male students, with a percentage ratio of 87.8% and 79.3%. It can be concluded that, in general, students have a high level of sustainability awareness. The results of this preliminary research on the level of sustainability awareness are expected to be a reference for the author in designing and developing ESD-based teaching materials on biotechnology to improve students' understanding of SDGs.